Pengaruh Perbandingan Terigu dan Tepung Ampas Tahu Terhadap Karakteristik Donat - Alfarisi, Hafizh; Permana, I Dewa Gde Mayun; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
Donuts are a snack food made from wheat. The availability of wheat in Indonesia is entirely supplied from abroad, so it is necessary to reduce the use of wheat by finding alternatives to the use of other flours that can replace wheat flour, one of them is tofu dregs flour because it has high nutritional and fiber content.This study was aimed to determine the effect of comparison of wheat and tofu dregs flour on the characteristics of donuts and to determine the right ratio of wheat and tofu dregs flour to produce donuts with the best characteristics. This study used a completely randomized design with treatment ratio of wheat and tofu dregs that consist of 5 levels, namely 100:0, 95:5, 90:10, 85:15, 80:20 percent. The data were analyzed using variance analysis and if the treatment had a significant effect then it was continued with Duncan's test. The results showed that the ratio of wheat and tofu dregs flour had a significant effect (P<0.05) on moisture, protein content, fat content, carbohydrate content, crude fiber content, volume of development, hardness, and sensory properties of the product, but had no significant effect ( P>0.05) on the ash content of the product. The treatment ratio of 95 percent wheat and 5 percent tofu dregs flour produced donuts with the best characteristics, namely with moisture content 26.34 percent, ash content 1.95 percent, protein content 8.96 percent, fat content 27.65 percent, carbohydrate content 35.10 percent, crude fiber content 1.65 percent, volume of development 210.29 percent, hardness 2.43 N, with color, aroma, taste, texture and overall acceptance preferred by the panelists.